PENGARUH DISIPLIN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII SMP TAMAN SISWA PEMATANGSIANTAR - Indah Sopyana Hutajulu; Anton Luvi Siahaan; Paulina H.N Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to obtain knowledge regarding the influence of learning discipline and learning motivation on learning outcomes in social studies subjects in class VIII SMP Taman Siswa Pematangsiantar.This research is quantitative type with the testing media used is SPSS 24. The sampling technique used saturated sampling for 76 respondents. The data collection technique used was a questionnaire. Instrument testing uses normality tests and reliability tests. The data analysis technique uses classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing, namely multiple linear regression analysis, t-test, f-test, and coefficient of determination.Data from research and management of partial test data (t-test) shows that the variable The variable Simultaneous test data management (f-test) shows that F_count is 5.582 > F_table is 3.12, so it can be concluded that learning discipline and learning motivation have a positive and significant effect on student learning outcomes.